If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x-1)=3x+2
We simplify the equation to the form, which is simple to understand
3(x-1)=3x+2
Reorder the terms in parentheses
+(+3x-3)=3x+2
Remove unnecessary parentheses
+3x-3=+3x+2
We move all terms containing x to the left and all other terms to the right.
+3x-3x=+2+3
We simplify left and right side of the equation.
0x=+5
0=5
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| 8x+8=8x+12 | | 4r+15=4r+11 | | 4xy*6xy= | | -2(4x+5)-11=-5 | | 2x-2=x+x | | 23x-8-14x=10 | | 2(b+8)-9=9 | | 2x^2=-144 | | 3k^2-11k-20=0 | | (8x^3)(2)= | | -8b+9+6b=3b+14 | | (4xy)(6xy)= | | 1+7=43+x | | 234x-67=56 | | y-2=y+3 | | 4(5x-7)-8x=-5 | | 4xy+6xy= | | 6x+24=12x+14 | | 6x-(4x+7)= | | 5a+4(2a+4)= | | 3y-9y=102 | | 344x-78=78 | | 3x^2+3=6x | | 1. 3+8x+7=34 | | 2345x=567 | | 2345x-567=567 | | (x+3)2=(x+5)3 | | 4t^4+8-(3t^4+5)= | | x+5=x+(9-x) | | 2x^2-12x=14 | | 4(x+8)=6x+8 | | 13+x*12-18=271 |